An ethnographic reflection on Muslim-Christian dialogue in the North of France: the context of lai͏̈cité - Brown, Malcolm D. (Islam and Christian-Muslim relations, 2002)
This article argues that laïcité is one of the most important issues facing Muslims in France, and French society as a whole. It contains an analysis of the historical meaning of laïcité, its relationship with secularization and secularity and the effect it has had on Muslims in contemporary France. Although laïcité and some of its interpretations have been causes of tense relations between Muslims in France and the rest of French society, the alliances and divisions which have emerged have not always been along confessional lines. As well as Muslims having a diversity of attitudes towards laïcité, members of other religions are faced with similar challenges. Openness and dialogue between Muslims and Christians in France appear to have increased in recent years, perhaps beyond other countries in Europe, and this article hypothesizes that this is due to the common challenge of laïcité . More precisely, dialogue in France is practical, formal and bilateral, in contrast to the United Kingdom, for example, where it is theoretical, informal and multilateral. These hypotheses are supported by establishing the social significance of Muslim-Christian dialogue, and by citing published experiences and analyses of Muslim-Christian dialogue, qualitative research which I undertook in the Lille area and comparative ethnography (the point of comparison being the United Kingdom, the ethnography concentrated in Glasgow). This article insists on the complexities of relations between Muslims, Christians, French society and laïcité, and examines their nature and significance. The common challenge of laïcité and the process of inter-religious dialogue are themselves complex phenomena, and this contributes to the specific alliances and divisions which can be seen.